ANALISIS MEMBENTUK TANGGUNG JAWAB SISWA MELALUI DISIPLIN BELAJAR DI SMA - Heru, Heru; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Â AbstractThis thesis is entitled "Students 'Learning Discipline Analysis in Forming Students' Responsibilities in Class X PPKn Subjects in 02 Raya Raya High School, Sungai Raya, Kubu Raya Regency". The method used in this research is descriptive research method, the form of research used is qualitative research. The subjects of the study were the tenth grade students of SMA Negeri 02 Sungai Raya, Kubu Raya Regency. Data collection techniques used in research are direct communication techniques, observation. The results of the study are: 1) Based on the results of the study relating to the learning of PPKn class X in SMA Negeri 02 Sungai Raya, Kubu Raya Regency, it was carried out well where the learning took place in accordance with the learning plans made by the teacher. 2) Based on the results of research related to students' learning discipline in Class X PPKn subjects at SMA Negeri 02 Sungai Raya, Kubu Raya Regency when the learning process, as a whole has been disciplined but there are still some students who lack discipline that can be seen in the learning process take place students are still out of the classroom, so the learning process is interrupted by students who are not disciplined the learning process is less focused in following teaching and learning activities. 3) Based on the results of research into the implementation of the discipline of learning in shaping the character of the responsibility of students of Class X IN SMA Negeri 02 Sungai Raya, Kubu Raya Regency will have an impact on the character of students in the discipline and responsibility, this can be seen from the violations committed by students, the impact of affecting learning outcomes as well as the learning achievements of students themselves.Â Keywords: Learning Discipline, PPKn Responsibility, Students